A simulator for percutaneous hepatic microwave thermal ablation under ultrasound guidance. (November 2014) - Wu, Wenbo; Xue, Yingfeng; Wang, Dong; Xue, Jin; Zhai, Weiming; Liang, Ping
Abstract The purpose of this study was to provide a simulation therapy environment for microwave thermal ablation (MWA) under the guidance of ultrasound, and to present an inexpensive and portable simulator built on real patient-based pre-operative computed tomography (CT) data. We established an experimental simulation system for teaching MWA and present the results of a preliminary evaluation of the simulator's realism and utility for training. The system comprises physical elements of an electromagnetic tracking device and an abdominal phantom, and software elements providing three-dimensional (3D) image processing tools, real-time navigation functions and objective evaluation function module. Details of the novel aspects of this system are presented, including a portable electromagnetic tracking device, adoption of real patient-based pre-operative CT data of liver, operation simulation of MWA, and recording and playback of the operation simulation. Patients with liver cancer were selected for evaluation of the clinical application value of the experimental simulation system. A total of 50 consultant interventional radiologists and 20 specialist registrars in radiology rated the simulator's hardware reality and overall ergonomics. Results show that the simulator system we describe can be used as a training tool for MWA. It enables training with real patient cases prior to surgery, and it can provide a realistic simulation of the actual procedure.